Spectrophotometric Determination of Trimethoprim in Pure Form and Pharmaceutical Formulations with Metol and potassium hexacyanoferrate (ΙΙΙ) - M.R. Raauf, Ayad (Tikrit Journal of Pharmaceutical Sciences, 2023)
A simple, sensitive and accurate spectrophotometric method of determination of trimethoprim (TMP) in pure form and pharmaceutical formulation. The method is based on the formation of (TMP) complex. The reaction between of the trimethoprim with the mixture of metol and potassium hexacyanoferrate (ΙΙΙ) was evaluated for the spectrophotometric determination of the trimethoprim. The maximum absorbance of the colored complex occurred at λ=540nm. Reaction conditions have been optimized to obtain (TMP) complex of high sensitivity and longer stability. Under optimum conditions the absorbance of the (TMP) complex where found to increase linearly with increase in concentration of the trimethoprim, which corroborated with correlation coefficient value. The concentration ranges are 10-100 µg mL-1 with detection limit 0.0286 µg mL-1 and relative standard deviation 0.74 % and relative error of prediction for drug were lower . The proposed method was successfully applied to determine of the selected trimethoprim in pure form and pharmaceutical formulations with good precision and accuracy compared to standard method as revealed by t- and F- values and the results obtained agree well with the labeled contents.